2000
DOI: 10.1002/1097-0142(20000715)89:2<334::aid-cncr18>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of macrophage migration inhibitory factor predicts the prognosis of patients with adenocarcinoma of the lung

Abstract: The results of the current study suggest that intracellular MIF distribution predicts patient prognosis in individuals with adenocarcinoma of the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 23 publications
3
55
3
Order By: Relevance
“…Overexpression of MIF has been identified in prostatic lymph node metastases (Meyer-Siegler and Hudson, 1996), human melanomas (Shimizu et al, 1999), breast carcinomas (Bini et al, 1997), adenocarcinomas of the lung (Kamimura et al, 2000), bladder cancer (Meyer-Siegler et al, 2004) and hepatocellular carcinomas (Akbar et al, 2001;Ren et al, 2003a). It has been shown that high levels of MIF significantly correlate with an unfavorable outcome in esophageal squamous cell carcinoma (Ren et al, 2005) and hepatocellular carcinoma (Ren et al, 2003a) and other tumors (del Vecchio et al, 2000;Meyer-Siegler, 2000;Tomiyasu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MIF has been identified in prostatic lymph node metastases (Meyer-Siegler and Hudson, 1996), human melanomas (Shimizu et al, 1999), breast carcinomas (Bini et al, 1997), adenocarcinomas of the lung (Kamimura et al, 2000), bladder cancer (Meyer-Siegler et al, 2004) and hepatocellular carcinomas (Akbar et al, 2001;Ren et al, 2003a). It has been shown that high levels of MIF significantly correlate with an unfavorable outcome in esophageal squamous cell carcinoma (Ren et al, 2005) and hepatocellular carcinoma (Ren et al, 2003a) and other tumors (del Vecchio et al, 2000;Meyer-Siegler, 2000;Tomiyasu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…MCM2 has been considered a promising lung tumour marker and perhaps even a marker for premalignant lesions (Tan et al, 2001), whereas tenascin has been proposed as a stromal marker for lung cancer (Kusagawa et al, 1998). Also MIF mRNA and protein levels have been found to be elevated in lung adenocarcinoma specimens (Kamimura et al, 2000) and TOP2A inhibitors are widely used as chemotherapeutic agents in lung cancer treatment (Kellner et al, 2000).…”
Section: Up-regulated Genesmentioning
confidence: 99%
“…Recently, increasing evidence has shown that MIF has a key role not only in the immune response but also in tumor growth and progression. MIF overexpression has been identified in prostatic lymph node metastases, breast carcinoma, adenocarcinomas of the lung, bladder cancer and hepatocellular carcinomas (Meyer-Siegler et al, 1996;Bini et al, 1997;Shimizu et al, 1999;Kamimura et al, 2000;Ren et al, 2003;Meyer-Siegler et al, 2004). A reduction in tumor-associated MIF expression resulted in decreased cell proliferation (Hudson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%